REKONSTRUKSI MANAJEMEN PENDIDIKAN PESANTREN - Untung, Moh. Slamet (Forum Tarbiyah, 2011)
Through intellectual discourse concerning the standardizationof the Islamic yellow book or the intellectual heritage of classicalIslam, pesantren (Islamic boarding school) institutionalizes thedynamics of its thinking. Islamic boarding school also continues tomove in building and shaping community attitudes to be more able tostand on the dimensions of ethical/moral in its life. In this perspective,undeniably, educational institution of Islamic boarding school hasadequately tested to survive, therefore it can move Islamic boardingschool up into a moral and spiritual ‘workshop’, as well as a center ofIslamic intellectual assessment and development of classical archipelagoas had ever reached its golden peaks in the Islamic worldcivilization. This reality provides a strategic significance for Islamicboarding school in the process of nation building. Therefore, with theintention that Islamic boarding school is still survive (in the otherword, is not “dead”) and in prefenting that Islamic boarding schoolwill be left by its supporters of community, Islamic boarding schoolmust take anticipatory strategic measures. These are done, amongothers is by doing the review for the management of Islamic boardingschool, even to perform reconstruction of managerial education ifit is required, regarding institutional systems, and other educationalfacilities. This paper attempts to discuss and review issues relating tothe crucial reconstruction of educational management of Islamicboarding school